Online learning experiences among nursing and midwifery students during the Covid-19 outbreak in Ghana: A cross-sectional study. Issue 12 (December 2022) - Addae, Hammond Yaw; Alhassan, Afizu; Issah, Shirley; Azupogo, Fusta
Abstract: As a result of the COVID-19 pandemic, schools in Ghana were compelled to suspend routine learning activities and shut down to avert a possible public health crisis. As such, online learning was introduced as a temporary measure to ensure continuity in learning. For nursing and midwifery students who are usually more engaged in face-to-face practical learning, it will be interesting to ascertain how they experienced online learning during the COVID-19 pandemic in a technologically deprived country. Hence, data was collected from March to June 2021 using online methods and a cross-sectional study design among students of nursing and midwifery training colleges in the five regions of Northern Ghana. Logistic regression and descriptive analysis were conducted using SPSS (version 22) to determine the association between (1) socio-demographic factors, (2) internet exposure and accessibility factors, and the outcome variable; students' experiences. The results for 318 students revealed that pleasant experiences were below average (42.8%) and that reliable college internet connectivity, older age, year of study, and residence in southern Ghana were significant predictors of pleasant experiences. However, high cost of data and home distractions were identified as the main challenges to online learning. Therefore, it is important for nursing and midwifery training colleges in northern Ghana to establish robust information and communication technology infrastructure on their campuses to ensure reliable internet connectivity. Abstract : Online learning experiences; Nursing and midwifery education; Internet connectivity; COVID-19 outbreak in Ghana.